2016
DOI: 10.5455/ijmsph.2016.17072015160
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on self-medication practices among the rural population of Meghalaya

Abstract: Klemenc-Ketis Z, Mitrovic D Patients' use of and attitudes towards self-medication in rural and remote Slovenian family medicine practices: a cross-sectional multicentre study Introduction: Self-medication is very common in the general population, but its prevalence can differ according to the place of residence. The aim of this study was to determine the prevalence of self-medication in patients attending rural and remote family physicians, and to detect the important factors that are associated with it. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 15 publications
5
20
2
2
Order By: Relevance
“…Antipyretic, analgesics and antacids are most commonly used drugs for selfmedication. (Parakh, Sharma, Kothari, Parakh, & Parakh, 2013) (Marak, Borah, Bhattacharyya, & Talukdar, 2016). The study conducted in Kathmandu Valley, Nepal showed that non-steroidal analgesic, antiinflammatory and antipyretic drugs were mostly preferred for the treatment of fever and headaches.…”
Section: Self-medication In Over the Counter And Prescription Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Antipyretic, analgesics and antacids are most commonly used drugs for selfmedication. (Parakh, Sharma, Kothari, Parakh, & Parakh, 2013) (Marak, Borah, Bhattacharyya, & Talukdar, 2016). The study conducted in Kathmandu Valley, Nepal showed that non-steroidal analgesic, antiinflammatory and antipyretic drugs were mostly preferred for the treatment of fever and headaches.…”
Section: Self-medication In Over the Counter And Prescription Drugsmentioning
confidence: 99%
“…Patients were also not fully aware about the ill effects of self-medication such as adverse drug reaction, drug-drug interactions, and other side effects. (Parakh, Sharma, Kothari, Parakh, & Parakh, 2013) (Marak, Borah, Bhattacharyya, & Talukdar, 2016) (Nair, Rajmohanan, & Kumaran, 2013).…”
Section: Self-medication In Over the Counter And Prescription Drugsmentioning
confidence: 99%
“…According to such studies, level of education, pervious experience of self-medication, occupation, lack of medical insurance, lack of time to visit physicians, low income [23–25], female sex [26], urban residece [27], youth age [28] and men [29, 30] were factors associated with SMP. Despite the negative consequences of self-medication and its high spread, studies on its prevalence and associated factors in this study area are limited.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of self-medication practice in different countries was ranged from 39% to 94% [17][18][19][20][21][22][23][24][25]. The prevalence in this study was 90.7% which suggests that self-medication practice in Sana'a city is among the highest.…”
Section: Discussionmentioning
confidence: 75%
“…This was expected as the pharmacy is the main supply for medication. Other sources like family member [18,20,23] and media [21] were found to be common in other studies as well.…”
Section: Discussionmentioning
confidence: 92%